Photocatalytic degradation of methylene blue using a zinc oxide-cerium oxide catalyst - Vuppala, Venkatesham; Motappa, Madhu Gattumane; Venkata, Satyanarayana Suggala; Sadashivaiah, Preetham Halugondanahalli (European Journal of Chemistry, 2012)
The photocatalytic degradation of methylene blue in aqueous solution was studied using a UV source in the presence of zinc oxide-cerium oxide (ZnO-Ce2O3) as photocatalyst, which was synthesized by a gel combustion technique and characterized by X-ray diffraction, scanning electron microscopy, and energy dispersive X-ray spectroscopy. The particle size of the catalyst was found to be in between 45 to 60 nm. The effects of catalyst loading (1.0-8.0 g/L), pH (4.0-9.2) and dye concentration (5.0-20.0 mg/L) on the degradation were studied in a batch reactor. The degradation rate was found to be strongly dependent on these experimental parameters. Appreciable degradation of methylene blue was achieved when the catalyst was calcined before use. Best results were observed with a catalyst loading of 5 g/L at pH = 9.2.